ADVERSE MATH ATTITUDES IN THE POST-PRIMARY EDUCATION OF RIVER STATE, NIGERIA: CAN METACOGNITION DO THE MAGIC? - Joyce Adaobi , Okoro (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2023)
There is growing concern about the increasing adverse attitude towards mathematics in Nigeria's educational system. Numerous research has underscored appropriate steps to address the challenge of mathematics attitudes. However, little is known about the role of metacognitive teaching in promoting healthy math attitudes. The present study employed a quasi-experimental design to examine the effect of the metacognitive instruction approach on students' mathematical attitudes in River State. Ninety-one (n = 91) students comprising males and females between the ages of 10 and 14 years with a mean age of (M=9.14) and (SD= 1.24) were randomly selected from different public secondary schools in River State as the study participants. The participants were grouped into two and were subjected to a pre-test and post-test study. The independent t-test conducted on the data following the pre-test and post-test studies proved that Metacognition enhanced the participants' mathematical attitudes at MD = 13.65 (95% CI, 8.91 to 16.17), t (89) = 6.328, p = .001. Thus, the result supported the study's hypothesis. It was concluded that Metacognition is effective in enhancing students' mathematics attitudes. The study recommends that teachers be regularly trained in using the metacognitive approach in the classroom.